An All-Optical Plasmon Modulator with a High Extinction Ratio Based on the Resonance of a Silver Block - Jimi Fang; Sisi Yang; Xuefang Hu; Changgui Lu; Mengjia Lu (Photonics)
Conventional all-optical modulators based on surface plasmon polaritons (SPPs) primarily utilize the nonlinear effect of a given material for modulation. Their performance is heavily dependent on the optical properties of the dielectric materials used and requires high pumping power. However, manipulating SPPs by controlling electron concentrations offers a material-independent approach suitable for all-optical modulators. In this paper, we propose a hybrid gold–ITO–silver block structure integrated within a Mach–Zehnder interferometer configuration to address this problem. The gold–ITO interface effectively localizes propagating SPPs. The pump light excites localized surface plasmons (LSPs) in the silver block, generating surface electric fields that modulate the electron concentration in the adjacent ITO layer. The extinction ratio is 50.8 dB when the electron concentration changes by 3.3 × 1020 cm−3, indicating that this structure is an all-optical modulator with a high extinction ratio. This approach shows significant promise for reducing pump power and enhancing the performance of all-optical modulators.